Vocation and social context - Giordan, Giuseppe (Religion and the social order ;, 2007)
Illustrating the different ways in which "vocation-profession" can be interpreted, and how it can be studied from various perspectives and with different scientific sensibilities, this book demonstrates how the concept of Beruf continues to be fertile for contemporary sociology